Giant Condyloma Acuminata with Maggots in Perianal Area of HIV Infected Male Running Head: A Case Report of Giant Condyloma Acuminata - Parajuli, Sudip; Shrestha, Amrita; Paudel, Upama (Journal of Nepalgunj Medical College, 2019)
We report a case of 28-year-old HIV-positive male with giant condyloma acuminata in anogenital region. This homosexual patient presented with a large foul smelling growth along with maggots in a perianal region refractory to treatment at presentation. The patient was successfully managed with excision and there was no recurrence of lesion at last follow-up at 2-months. The case highlights the rare presentation and management of difficult-to-treat case of giant condyloma acuminata with maggots of anogenital region in HIV-positive patients.